Public Policies and Work Integration Social Enterprises: The Challenge of Institutionalization in a Neoliberal Era - Cooney, Kate; Nyssens, Marthe; O’Shaughnessy, Mary; Defourny, Jacques (Nonprofit policy forum, 2016)
One particular field of Social Enterprise – WISEs or Work Integration Social Enterprises – has become increasingly recognised as being emblematic of the dynamics of social enterprises and now constitutes a major sphere of their activity globally. From their early roots, focusing on providing productive activity for the blind and those with other physical and/or intellectual disabilities, WISEs are pioneers in promoting the integration of excluded persons through a productive activity. In recent decades, WISEs have incrementally evolved as a tool for implementing national and regional labour market policies. The papers in this special edition explore how populations of WISEs in different country contexts have emerged, and in some instances, shifted in their identities over time in relation to changing national or regional public policies. This special issue is part of the ICSEM project, a worldwide research project aiming to identify, analyze and compare social enterprise models across countries, regions and fields. The special issue features five country specific analyses from the first stage of the ICSEM project where researchers focusing on WISEs examined the policy environment surrounding WISEs and the heterogeneity of the organizational WISE models that have emerged in different contexts: Ireland, the United States, Japan, Austria and Switzerland.